Causality between major depressive disorder and functional dyspepsia: a two-sample Mendelian randomization study - Yaming Du; Rui Wang; Rui Wang; Xinzi Xu; Junli Wang; Wei Shao; Guohua Chen; Guohua Chen (Frontiers in Neurology, 2024)
BackgroundTo investigate the causal relationship between major depression and functional dyspepsia using two-sample Mendelian randomization.MethodsData for major depression and functional dyspepsia were obtained from genome-wide association studies. We selected Single Nucleotide Polymorphisms (SNPs) strongly associated with severe depression. Mendelian randomization analysis was conducted using methods such as Inverse-Variance Weighted (IVW), MR-Egger, and Weighted Median Estimator (WME). Sensitivity analysis was performed to assess the robustness of the results.ResultsA total of 31 eligible SNPs were identified as instrumental variables for major depression. IVW analysis indicated a positive causal relationship between the two conditions (β = 0.328; SE = 0.137; p = 0.017), suggesting that severe depression increases the risk of functional dyspepsia (OR = 1.389; 95% CI: 1.062–1.816). Sensitivity tests showed no evidence of heterogeneity or horizontal pleiotropy (p > 0.05).ConclusionMR analysis had shown that major depressive disorder is associated with an increased risk of functional dyspepsia.